Solvent-engineered performance improvement of graphene quantum dot sensitized solar cells with nitrogen functionalized GQD photosensitizers. (1st April 2022) - Dey, Tamal; Ghorai, Arup; Das, Soumen; Ray, Samit K.
Graphical abstract: Photo Conversion Efficiency of Solvent Engineered and Nitrogen Functionalized Graphene Quantum Dots Sensitized Solar Cells. We discussed compositional, optical and electronic properties of N-GQDs synthesized in different solvents, and their role in the photoconversion efficiency of quantum dots sensitized solar cells (QDSSCs). Solar cells fabricated from R-GQDs synthesized in DMF solvent show much superior performance (∼5.3%) compared to the solar cells fabricated from G-GQDs (∼0.7%) synthesized in water solvent, which is attributed to higher Jsc, Voc and fill factor. Highlights: N-GQDs are used as non-toxic and highly-stable photosensitizers in QDSSC. N-GQDs were synthesized in different solvents i.e·H2 O (G-GQDs) and DMF (R-GQDs) Solvents used strongly influence photo-physical and electronic properties of N-GQDs. R-GQDs facilitate more light absorption and better charge transport than in G-GQDs. R-GQDs used as photosensitizer in QDSSC exhibit photoconversion efficiency of > 5% Abstract: W e report for the first time that the choice of solvent used in the synthesis of nitrogen-doped graphene quantum dots (N-GQDs) has a significant effect on the photovoltaic performance of quantum dot sensitized solar cells (QDSSC) where N-GQDs work as photosensitizers. Switching from protic water (H2 O) solvent to aprotic N-N dimethylformamide (DMF) causes significant change in structural, photophysical and electronic properties of N-GQDs working as active materials in QDSSC. Unlike traditional dye-sensitized solar cells, N-GQDs replace toxic and readily degradable organic dyes as an active material, due to enhanced stability, cost-efficient fabrication, and environment-friendly processing. We discussed compositional, optical, and electronic properties of N-GQDs synthesized in different solvents, and their role in the photoconversion efficiency of quantum dots sensitized solar cells. Spectroscopic results reveal that nitrogen-doped graphene quantum dots with green emission (G-GQDs) have relatively shorter effective conjugation length and lower content of pyrrolic nitrogen groups because water is a polar protic solvent, which suppresses the water elimination reaction by donating protons to the reaction medium. On the contrary, DMF, a polar aprotic solvent, cannot donate hydrogen, leading to enhanced nitrogen units in the graphene quantum dots framework and red emission (R-GQDs), thus improving carrier density and transport properties. QDSSCs fabricated from R-GQDs exhibit photovoltaic performance (PCE > 5.0%) superior to other previously reported GQD sensitized solar cells.